Assessment of safety status of shield tunnelling using operational parameters with enhanced SPA. (May 2022) - Lyu, Hai-Min; Shen, Shui-Long; Zhou, Annan; Yin, Zhen-Yu
Highlights: A risk status model of shield tunnelling is developed using operational parameters. The model integrates enhanced SPA with interval-based fuzzy numbers. A field tunnelling case in Shenzhen Airport is used to validate the proposed model. Assessed results indicated that high-risk sections is related to cutter exchange. Results provide guide for risk warnings and management during shield tunnelling. Abstract: This study investigates the safety status for a shield machine during tunnelling. An enhancement of the existing set pair analysis (SPA) method incorporating with interval-based fuzzy numbers is proposed to assess the safety status. The enhanced SPA overcomes the limitation of a judgment procedure concerning the positive or negative characteristic of a risk factor in existing SPA. The assessed results were validated by the high-risk sections related to cutter exchange in field construction. The percentage of the risk levels III and IV obtained from the enhanced SPA is greater than that from the existing SPA. The comparison indicates that the enhanced SPA is more effective to identify higher risks than the existing SPA methods. Meanwhile, the SPA methods are firstly used to assess the construction risk using shield parameters, and the enhanced SPA is better than the existing SPA methods during application.